-23=3e-(-9)

Simple and best practice solution for -23=3e-(-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23=3e-(-9) equation:


Simplifying
-23 = 3e + -1(-9)

Multiply -1 * -9
-23 = 3e + 9

Reorder the terms:
-23 = 9 + 3e

Solving
-23 = 9 + 3e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-3e' to each side of the equation.
-23 + -3e = 9 + 3e + -3e

Combine like terms: 3e + -3e = 0
-23 + -3e = 9 + 0
-23 + -3e = 9

Add '23' to each side of the equation.
-23 + 23 + -3e = 9 + 23

Combine like terms: -23 + 23 = 0
0 + -3e = 9 + 23
-3e = 9 + 23

Combine like terms: 9 + 23 = 32
-3e = 32

Divide each side by '-3'.
e = -10.66666667

Simplifying
e = -10.66666667

See similar equations:

| 2x+12-10=12+4x-4 | | z+18=y | | 2+5t=-5 | | 10w-18=42 | | 18s^3=50s | | -4(4y-6)-y=-2(y-2) | | x^2-2x+25=0 | | 65=k+8 | | 2thidsx=10 | | 3d+5=17 | | 3(4-2)-(12+3x)=18 | | 3x-2y=-11 | | 11d+13=-9 | | 3+5a=9-3a | | 7x-12=4(x-2) | | -19=35+9x | | y+2=3(x+1) | | 4(l-8)+20=5 | | 3x-8=2x+12 | | 4.3-1.4(p+7)=9.7 | | y-(-2)=-1(x-1) | | X^2-7x-3=0 | | (2x-2)5=3x | | 8.6t-5.7=-1.7+7.6t | | 1-3b=2b-8 | | 2c+12=5c-27 | | -27=-3p+15-3p | | x+10x=-5 | | 6-3x=21 | | n^3-6n^2-n+6=0 | | -2.4+1.2+1.2=4.8 | | 7x+5n=10(x-7)-3x |

Equations solver categories